New and poorly known Pleurota Hübner, [1825] species from peninsular Spain, the Balearic Islands, and the Canary Islands (Lepidoptera: Oecophoridae, Pleurotinae) - Jukka Tabell; Martin Honey; Théo Leger; Marko Mutanen; Timo Nupponen; Pasi Sihvonen (SHILAP)
Four new Pleurota Hübner, [1825] species from peninsular Spain, one species from the Balearic Islands and one species from the Canary Islands are described: P. rondaensis Tabell & Nupponen, sp. nov., P. pyrenaella Tabell, sp. nov., P. balearica Tabell & Honey, sp. nov., P. malagaensis Tabell & Nupponen, sp. nov., P. grancanariella Tabell, sp. nov. and P. subnobilella Tabell, sp. nov. In addition, adults, and genitalia of seven poorly known Spanish Pleurota species are illustrated, most of them for the first time, and photos of several type specimens are presented. Lectotypes for P. protasella Staudinger, 1883, P. glitzella (Staudinger, 1883), P. pleurotella (Staudinger, 1871), P. sobriella (Staudinger, 1859) and P. nobilella Rebel, 1901 are designated. DNA barcodes of the aforementioned species are compared with those of all other Pleurotinae available to us in the BOLD database. Each of the species studied herein has a unique BIN (Barcode Index Number).